ANALISIS BENTUK DAN ORIENTASI KURIKULUM DALAM MENINGKATKAN KUALITAS PENDIDIKAN - Saskia Azzahra; Anitha Yuniar; Azzahra Saskiyah (Jurnal Manajemen Pendidikan, 2026)
This study aims to evaluate various curricula and curricular directions implemented within educational systems—particularly in Indonesia—to serve as a foundation for developing learning processes that align with scientific advancements, societal needs, and global challenges. A literature review method was employed, analyzing scholarly references such as books, journals, and educational documents pertaining to curriculum theory and development. The findings identify four types of curricula—subject-based, correlated, integrated, and student-centered—each possessing distinct characteristics, advantages, and limitations regarding the support of the learning process. Furthermore, curriculum design emphasizes specific objectives, learners, instructional materials, and societal needs. Curricular evolution in Indonesia reflects a shift from teacher-centered to student-centered instructional approaches, a transition evident in the implementation of the *Kurikulum Merdeka* (Independent Curriculum). The study’s novelty lies in its analysis, which integrates a discussion of curriculum structure and direction with the implementation of *Kurikulum Merdeka* as an example of curriculum enhancement responsive to 21st-century competency requirements. The findings are expected to serve as a reference for educators in designing efficient and adaptive learning experiences focused on improving the quality of education.